Three essays on international trade and policy - Chen, Bowen (Kansas State University, 2019)
International trade in agricultural and food commodities has grown rapidly during the past five decades, with increasingly more countries participating in the international mar- kets either as food importers or as food exporters. Despite the fast growth, international agricultural trade, however, is still largely affected by various policy distortions. This is especially the case in developing countries, in which opening to the international market is often perceived to be in conflict with their policy objectives of ensuring food security. In this context, this dissertation constitutes three essays toward better understanding of how international trade is affected by policy and how it can affect food security in developing countries. The first essay conducts a case study with quantitative analysis regarding the trade policy for grain commodities in China. Specifically, China emerged as a grain importing country in mid 2000s. In 2016, the U.S., a major grain exporter, launched a trade dispute against China at the World Trade Organization, arguing that China has been restricting its grain imports via tariff quota administration. Despite the criticism of the U.S., little do we know about the extent to which the grain imports in China were actually restricted by its trade policy, mainly because China’s grain import behaviors have not been sufficiently studied. For instance, even the import demand elasticity, a key input into policy assessment, is unknown. To fill this gap in the literature, this article investigates impacts of the tariff quota administration on China’s grain imports from its trading partners. We estimate import demand elasticity for each grain commodity using a source differentiated import demand model and then use the elasticity estimates to quantify the policy impacts on trade. In particular, the tariff quota administration is treated as a non tariff barrier and measured by ad valorem tariff equivalents in the model. We find that the tariff quota administration might have reduced the quota fill rates for the grain commodities by 10-35% during 2013-2017 in China, and that the wheat imports from the U.S. were largely negatively affected. We also find that the tariff quota administration acts like an import variable levy – its import restrictiveness varies negatively with world prices, leading to lower import demand elasticities. The second essay concerns the trade impacts on food price variability in developing countries. In particular, we are interested in this question: do food imports increase the variability of domestic food prices? The question matters because if imports destabilize domestic prices, storing crops for future consumption may prove an appealing strategy to cope with the adverse supply effects of a more unstable climate. Unfortunately, public storage has proven to be unsustainable due to the high costs of carrying crop inventories over time and the inability of policy planners to correctly forecast changes in domestic supply. In this context, it is important to understand the roles of both imports and stocks in affecting domestic food price variability. Using maize prices observed in 76 maize markets of 27 maize net importers across Africa, Asia and Latin America during 2000-2015, we find that, on average, a 1% increase in the ratio of imports to total consumption is correlated with a 0.29% reduction of the intra-annual coefficient of variation of maize prices; likewise a 1% increase in the amount of maize available in stocks at the beginning of the season is correlated with a 0.22% reduction in the said coefficient. We also find that climate-induced supply shocks toward mid-century may increase maize price variability in the focus countries by around 10%. These increases, however, could be offset with similar increases in the ratio of imports to total consumption or in the stock-to-use ratio at the beginning of the crop marketing year. The third essay also concerns the trade impacts on food price variability in developing countries. Rather than focusing on the roles of imports and stocks, we look into the effects of foreign yield shocks on domestic food price variability in this essay. Around two thirds of developing countries are now net food importers. While enjoying economical food in the international market, these countries have become increasingly more concerned that their food price stability is now vulnerable to foreign yield shocks, which are expected to grow in frequency and intensity in the future due to the climate change. Yet, the extent to which foreign yield shocks could affect food price stability in the food-importing countries have not been explicitly quantified in previous studies. This article aims to fill the gap by estimating the effects of foreign maize yield shocks on domestic maize price variability. We perform the analysis using price data of 74 maize markets in 24 net food-importing countries during 2000-2016. We find that positive foreign yield shocks have negative effects on domestic price variability, meaning that domestic prices become more stable under positive foreign yield shocks. Negative foreign yield shocks, however, do not have significant effects on domestic price variability, except for causing higher price variability in a few landlocked countries. We also find that domestic maize price variability could increase in the coming decades due to the increasing variability of maize yields under climate change. Yet, most focus countries seem to have accumulated stocks sufficient enough to maintain stable prices. We conclude that food-importing countries benefit from the international market in domestic price stability, and that storage could be an effective policy tool to complement international trade for price stabilization.
Keywords: International trade; Climate change; Food security